STATE AND WAYS OF DEVELOPMENT OF RUSSIA IN THE WORLD MARKET OF SERVICES - D. I. Tkachenko (Вестник университета)
The current state and the most promising directions of Russia in international trade in services has been considered. The structure of export of Russian services, its dynamics and trends have been shown. Attention is focused on exports of transport, tourism, construction, high-tech and intellectual services, which make up the largest share of exports of services of the Russian Federation. Information on Russia ‘s position in the world service markets has been provided and factors affecting the competitiveness of Russian service providers have been listed. Trends in world trade in services have been analysed, the main problems preventing Russia’s expansion in the world services market have been enumerated and measures to strengthen the position of domestic exporters have been proposed. The role of the state influence on the development of services exports and this sphere in order to diversify the economy has been reviewed.